2014
DOI: 10.1007/s40750-014-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Are Preferences for Women’s Hair Color Frequency-Dependent?

Abstract: An individual's fitness depends not only on their phenotype but also on the phenotypes of their competitors and contemporaries. Sexual attractiveness may be strongly influenced by an individual's familiarity to potential mates or the rarity of the individual's phenotype. Such effects can cause negative frequency-dependent selection, maintaining striking polymorphisms in ornamentation. Here we test whether preferences for women's hair color, which is highly polymorphic between European populations, reflects pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 55 publications
(82 reference statements)
0
8
1
Order By: Relevance
“…The preference for blonde hair may be evident only in men, as it has been proposed in the ‘rare-color advantage’ hypothesis (Frost, 2006). Thus, our data cannot support the view on either a presence or absence of such an effect (see for a lack of evidence, Janif et al, 2015). One could argue that women assessing other women’s hair tend to ‘derogate’ them by assigning less positive statements to features that are admired by men due to intra-sexual competition (as it has been shown for female facial attractiveness, Fisher, 2004).…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The preference for blonde hair may be evident only in men, as it has been proposed in the ‘rare-color advantage’ hypothesis (Frost, 2006). Thus, our data cannot support the view on either a presence or absence of such an effect (see for a lack of evidence, Janif et al, 2015). One could argue that women assessing other women’s hair tend to ‘derogate’ them by assigning less positive statements to features that are admired by men due to intra-sexual competition (as it has been shown for female facial attractiveness, Fisher, 2004).…”
Section: Discussioncontrasting
confidence: 91%
“…Frost (2006) postulated the existence of a ‘rare-color advantage’ with regard to female hair. According to this view, those with a hair color of lower incidence in a given population should be perceived as more attractive than those with a hair color with greater incidence (but see Janif et al, 2015). Moreover, Sorokowski (2008) showed that men judged images of women with (digitally-enhanced) blonde hair significantly younger than the same images with brown hair (particularly in women around the age of 30).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, however, found that experimentally manipulating the frequency of women's hair color, which in European populations is highly polymorphic and thought to have evolved under frequency‐dependent sexual selection, does not impact on preferences (Janif et al. ). Future research is therefore needed in order to understand why time had a significant effect for opposite‐sex adiposity preferences.…”
Section: Discussionmentioning
confidence: 99%
“…, blonde hair did not receive the most positive judgments. However, there were no male panellists included in the study and a blonde preference may be evident only in men, as proposed in the ‘rare‐colour advantage’ hypothesis (; but see ).…”
Section: Introductionmentioning
confidence: 99%